A Comparative Study of the Electrical Characteristics of Piezoelectric and Triboelectric Nanogenerators for Energy-Harvesting Floor Tiles - Yingyong, Phonexai; Thainiramit, Panu; Nundrakwang, Songmoung; Janphuang, Pattanaphong; Isarakorn, Don (My University, 2020)
Piezoelectric and Triboelectric nanogenerators (PENG and TENG) have gained significant attention for use in self-powered electronics and sensing systems. They also have high potential to harvest energy from low-frequency vibration sources in the ambient environment. This paper investigated the performance and behavior of the two aforementioned nanogenerators based on energy-harvesting floor tiles by using a test bench to demonstrate the electrical characteristics output and comparing their power density output, energy density output, and other properties for characterization and scale-up in practical applications. The input used in the experiment varied the gap distance of the cover plate for the test bench with constant pneumatic pressure to excite the cover plate. The experimental results showed that the power density and energy density of PENG were higher than those of the TENG. The power density and energy density measured in 10 s under 2 Hz of input excitation of PENG and TENG at the gap width of 5 mm were 5773.35 μW/cm3, 1376.26 μJ/cm3 and 752.34 μW/cm3, 31.32 μJ/cm3, respectively. Due to their high output density, they enable promising possibilities to power small consumption electronics and sensing systems.
Keywords: energy-harvesting floor tile; low-frequency vibration energy harvesting; piezoelectric energy harvester; triboelectric energy harvesting